Educator Ethics from Perspective of Al-Imām Al-Ājurri Al-Baghdādī in The Book of Akhlāq Al-’Ulamā - Harahap, Fuad Hasan; Hanum, Azizah; Sapri, Sapri (Graduate Program Magister Manajemen Pendidikan, 2024)
This study aims to analyze the ethics of educator’s perspective al-Imām al-Ājurri al-Bagdādī in book of Akhlāq al-’Ulamā and analyze the relevance of educator ethics perspective al-Imām al-Ājurri al-Bagdādī in Kitāb Akhlāq al-’Ulamā with the current context. This type of research is qualitative research with a library research approach. Data analysis techniques using content analysis techniques. This research reveals critical aspects of educator ethics, including gratitude towards God, sincerity in seeking knowledge, respectful interactions with knowledgeable individuals, and humility in discussions. The study contributes by demonstrating the enduring applicability of al-Imām al-Ājurri al-Bagdādī’s teachings in guiding ethical conduct among educators, thereby providing valuable insights for contemporary educational settings. The findings underscore the importance of humility, sincerity, and moral integrity in fostering ethical leadership and creating meaningful learning environments, making a noteworthy contribution to the ongoing discourse on educator ethics.